The Prosodic Characteristics of Non-referential Co-speech Gestures in a Sample of Academic-Lecture-Style Speech - Shattuck-Hufnagel, Stefanie; Ren, Ada (Frontiers in Psychology, 2018)
Many studies have documented a close timing relationship between speech prosody and co-speech gesture, but some studies have not, and it is unclear whether these differences in speech-gesture alignment are due to different speaking tasks, different target gesture types, different prosodic elements, different definitions of alignment, or even different languages/speakers. This study contributes to the ongoing effort to elucidate the precise nature of the gesture-speech timing relationship by examining an understudied variety of American English, i.e. academic-lecture-style speech, with a focus on an understudied type of gesture: Non-Referential gestures, which make up the majority of this corpus. Results for the 1334 stroke-defined gestures in this 20-minute sample suggest that the stroke phase of a non-referential gesture tends to align with a pitch-accented syllable, just as reported in studies of other gesture types (e.g. deictic gestures) and in other speaking styles (such as narration). Preliminary results are presented suggesting that trajectory shapes of these Non-Referential gestures are consistent across a higher-level prosodic grouping, supporting earlier proposals for kinematic constancy across spoken prosodic constituents (Kendon 1972, 1980, 2004). Analysis also raises the possibility that the category of Non-Referential gestures is not solely made up of ‘beats’, defined as simple bi-phasic flick-like movements that beat out the rhythm of the speech, but includes gestures with multiple phases, a range of trajectory shapes and various types of rhythmicity. Taken together, the results of this analysis suggest 1) a wide variety of gesture configurations within the undifferentiated category of Non-Referential gestures or ‘beats’, which requires further investigation, and 2) a close coordination between co-speech gestures and the prosodic structure of spoken utterances across speaking styles and gesture referentiality, which has profound implications for modelling the process of planning an utterance. Keywords: co-speech gesture, speech prosody, speech production planning, prosodic prominence, prosodic constituents